1990
DOI: 10.1104/pp.93.4.1286
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Digalactosyldiacylglycerol in Plastids from 16:3 and 18:3 Plants

Abstract: Intact chloroplasts isolated from leaves of eight species of 16:3 and 18:3 plants and chromoplasts isolated from Narcissus pseudonarcissus L. flowers synthesize galactose-labeled mono-, di-, and trigalactosyldiacylglycerol (MGDG, DGDG, and TGDG) when incubated with UDP- [6-3H]galactose. In all plastids, galactolipid synthesis, and especially synthesis of DGDG and TGDG, is reduced by treatment of the organelles with the nonpenetrating protease thermolysin. Envelope membranes isolated from thermolysin-treated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
3
33
1
Order By: Relevance
“…The recombinant DGD2 protein uses UDP-Gal as the galactose donor and MGDG as the acceptor (26). MGDG in the absence of UDP-Gal did not lead to the formation of DGDG ruling out a GGGT activity originally proposed to be the major DGDG synthase activity in plants (21)(22)(23). By deleting the N-terminal domain it was recently demonstrated that the glycosyltransferase domain of DGD1 also utilizes UDP-Gal as the galactose donor (28).…”
Section: Digalactosyldiacylglycerol Synthasesmentioning
confidence: 99%
“…The recombinant DGD2 protein uses UDP-Gal as the galactose donor and MGDG as the acceptor (26). MGDG in the absence of UDP-Gal did not lead to the formation of DGDG ruling out a GGGT activity originally proposed to be the major DGDG synthase activity in plants (21)(22)(23). By deleting the N-terminal domain it was recently demonstrated that the glycosyltransferase domain of DGD1 also utilizes UDP-Gal as the galactose donor (28).…”
Section: Digalactosyldiacylglycerol Synthasesmentioning
confidence: 99%
“…Van Besouw and Wintermans [55], Heemskerk and Wintermans [56] and Heemskerk et al [57] have proposed that the galactolipid :galactolipid galactosyltransferase is indeed responsible for digalactosyldiacylglycerol synthesis. For instance, Heemskerk et al [57] analyzed galactolipid synthesis in chloroplasts or chromoplasts from eight species of 16:3 and 18:3 plants and found that digalactosyldiacylglycerol formation is never stimulated by UDP-Gal or any other nucleoside 5'-diphosphodigalactoside ; in all cases, digalactosyldiacylglycerol formation was reduced by thermolysin digestion of intact organelles. In vitro, the galactolipid :galactolipid galactosyltransferase does not show strong specificity for any monogalactosyldiacylglycerol molecular species.…”
Section: Biosynthesis Of Other Plastid Glycerolipids (Digalactosyldiamentioning
confidence: 99%
“…6A). Galactolipid:galactolipid galactosyltransferase is known to form DGDG by the transfer of a galactosyl group from one MGDG to another MGDG molecule (10,12). Its activity in spinach chloroplasts is inhibited by treatment of chloroplasts with the nonpenetrating proteinase thermolysin (10).…”
Section: Formation and Desaturation Of Prokaryotic Galactolipids In Smentioning
confidence: 99%
“…(c) Eukaryotic MGDG and DGDG are synthesized at similar rates. (d) Only two galactosyltransferases are known which synthesize galactolipids (10)(11)(12). (e) In vitro, either galactosyltransferase discriminates only moderately between various molecular species ofMGDG or DGDG, but polyenoic MGDG is galactosylated faster than oligoenoic MGDG(l1).…”
Section: Regulation Of Galactolipid Synthesis In Spinach Leavesmentioning
confidence: 99%
See 1 more Smart Citation